2017
DOI: 10.1038/s41598-017-02166-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled levitating clusters of water droplets: pattern-formation and stability

Abstract: Water forms ordered hexagonally symmetric structures (snow crystals) in its solid state, however not as liquid. Typically, mists and clouds are composed of randomly moving small droplets lacking any ordered structure. Self-organized hexagonally patterned microdroplet clusters over locally heated water surfaces have been recently observed. However, many aspects of the phenomenon are far from being well understood including what determines droplets size, arrangement, and the distance between them. Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 16 publications
(29 reference statements)
0
73
0
4
Order By: Relevance
“…[18][19][20][21] The main thrust of this hypothesis is the discovery that water clusters can organize themselves into stable patterns when in contact with magnetic fields or highly diluted solutes. [22][23][24][25] The identification of a potential electromagnetic "signature" in aqueous nano-structures formed in the dilution process (a phenomenon named "naneons" or "nano-associates") supports this hypothesis. [26][27][28][29] Recently Cartwright [30][31][32] has provided evidence for the electromagnetic hypothesis in which it has been demonstrated that solvatochromic dyes display changes in their ultraviolet/visible (UV/vis) spectra in the presence of ultra-dilute succussed solutions consistent with changes in dye polarity.…”
Section: ) Electromagnetic Field Hypothesismentioning
confidence: 80%
“…[18][19][20][21] The main thrust of this hypothesis is the discovery that water clusters can organize themselves into stable patterns when in contact with magnetic fields or highly diluted solutes. [22][23][24][25] The identification of a potential electromagnetic "signature" in aqueous nano-structures formed in the dilution process (a phenomenon named "naneons" or "nano-associates") supports this hypothesis. [26][27][28][29] Recently Cartwright [30][31][32] has provided evidence for the electromagnetic hypothesis in which it has been demonstrated that solvatochromic dyes display changes in their ultraviolet/visible (UV/vis) spectra in the presence of ultra-dilute succussed solutions consistent with changes in dye polarity.…”
Section: ) Electromagnetic Field Hypothesismentioning
confidence: 80%
“…Meanwhile, a vertically motionless droplet in a droplet cluster is embraced by the steam-air mixture, which is equivalent to the translational motion of the droplet in a fixed medium. A typical velocity of the flow supporting the droplet cluster is about 0.1 m s -1 [39]. It exceeds the maximal drift velocity 0.0123 m s -1 of the molecules falling onto the droplet (Fig.…”
Section: Fig 2 Surface Area Of a Droplet S As Function Of Time T Acmentioning
confidence: 86%
“…Recent studies have also demonstrated that micro-bubbles can form ordered relatively stable structures such as levitating clusters of microdroplet ( Fig. 4) with the number of droplets from one to hundreds [17,18]. Such clusters provide new ways to manipulate droplets and potentially can lead to new computational applications.…”
Section: Droplet Computersmentioning
confidence: 98%
“…Voronoi entropy, which is analogical to the Shannon entropy, is used to analyse information content of the clusters [17,18].…”
Section: Droplet Computersmentioning
confidence: 99%